A retrospective evaluation of condylar morphology using panoramic radiography in a sample of Turkish population - Peker Öztürk, Hilal; Ismail, Hakan Avsever; Şenel, Bu?ra; Ozgedik, Hatice Seda; Kurt, Mehmet Hakan (Via Medica, 2024)
Background: The temporomandibular joint is one of the most complex anatomic structures. It takes a great role in masticatory system and helps to make possible some functions such as speaking, chewing and swallowing. Clinicians should have sufficient anatomical knowledge to assess relationships of the hard and soft tissues, including the mandibular condyle, glenoid fossa, articular eminence of the temporal bone, the articular disc and its attachments. The aim of this study was to evaluate the frequency of different types of mandibular condyles and its distribution according to the age and gender. It was also evaluated whether the condyle types were bilaterally symmetrical or not. Materials and methods: A total of 1315 digital panoramic images which obtained from the patients suffering from the dental problems were assessed. Demographic data, condylar morphology were noted. All obtained data were analysed by using descriptive statistics. Morphology of mandibular condyles were classified into four shapes as identified in other studies, namely: type I - oval shape, type II - diamond shape, type III - bird beak shape, type IV - crooked finger shape. Two independent examiners, who have 19 and 7 years of experience in oral and dentomaxillofacial radiology, made a consensus and evaluated all images. Results: A total of 1315 digital panoramic images were assessed. Seven hundred sixty-seven [58.3%] the patients were female and 548 [41.6%] were male. The age range of patients was from 18 to 84 years. Right-left condyle types were found to be symmetrical in the range of 67% of the subpopulation examined in the study. For the consensus, 'oval' condyle was common on both the right and left, while 'crooked finger' condyle was the rarest. Conclusions: The temporomandibular joint is the most important structure for all jaw functions such as speech, swallowing. In order for all these functions to continue in a healthy way, the anatomical structure should be known very well down to the finest detail. Identification of anatomical structures and their variations can play an important role in implant dentistry. Clinicians commonly prefer conventional radiologic methods to evaluate dentomaxillofacial region. Although the most of the variations are asymptomatic and require no treatment, correct identification of these findings will reduce unnecessary further diagnostic assessments and will provide more appropriate treatment plans. © © 2024 Via Medica.
Keywords: anatomy; mandibular condyle; radiographic interpretation